2020
DOI: 10.1186/s12891-020-3143-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative injection of absorbable gelatin sponge (AGS) mixed with cement followed by spinal decompression to treat elderly with vertebral hemangiomas

Abstract: Background: Elderly patients with vertebral hemangiomas are rare and might require surgery. Thus, the choice of surgery for these lesions remains controversial because of the rarity of these lesions. This study aimed to analyze the clinical efficacy of the intraoperative injection of absorbable gelatin sponge mixed with cement followed by spinal decompression to treat the elderly with typical vertebral hemangiomas. The risk factors for hemangioma recurrence were investigated through a literature review. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In our clinical practice, we used preoperative trans-arterial embolization and intraoperative injection of gelfoam to further reduce blood loss.After injection of gelfoam and cement, the visualization of operative eld was clearer, and the tumor tissue can be removed more effectively and thoroughly. We previously found the intraoperative injection of absorbable gelfoam is associated with fewer blood loss and surgery duration [30]. Because the size of gelfoam particlesare small, the communicating blood vessels of the tumor body can be embolized by the gelfoam particles, and the mixed contrast medium injected at the same step can demonstrate the effect of embolization.…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical practice, we used preoperative trans-arterial embolization and intraoperative injection of gelfoam to further reduce blood loss.After injection of gelfoam and cement, the visualization of operative eld was clearer, and the tumor tissue can be removed more effectively and thoroughly. We previously found the intraoperative injection of absorbable gelfoam is associated with fewer blood loss and surgery duration [30]. Because the size of gelfoam particlesare small, the communicating blood vessels of the tumor body can be embolized by the gelfoam particles, and the mixed contrast medium injected at the same step can demonstrate the effect of embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Ben wang et al 15 Wei hong Xu et al 20 Cloran et al 3 Nair et al 16 Singh et al 19 Prabhuraj et al 18 Narayana et al 17 Zhang et al 21 (14.1%). CT guided alcohol ablation has been offered to those patients presenting with back pain and radicular symptoms or back pain alone 3 (6.0%).…”
Section: Itemsmentioning
confidence: 99%
“…5,6 Literature documents various management options for AVH including medical management, CT guided alcohol ablation, External beam radiation, Percutaneous vertebroplasty and Surgery with or without preop embolization. 3,16,19,20 Due to the wide array of treatment options, clinicians has decision dilemma in choosing the optimal line of management to maximise patient outcome . Nigro et al 7 in his editorial in Journal of Spine Surgery in the year 2017 has stated that AVH are common lesions with many unknown aspects and with no universal consent in its line of management.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported a decrease in postoperative drain output and length of hospital stay following the use of absorbable gelatin sponges in multilevel posterior lumbar fusion [39]. When mixed with cement, they can significantly reduce intraoperative blood loss and operative time in patients undergoing spinal decompressions for treatment of vertebral hemangiomas [40]. Preinjection of Gelfoam for embolization is another technique successfully being used in percutaneous vertebroplasties to minimize venous cement leakage [1].…”
Section: Mechanical Hemostatsmentioning
confidence: 99%